2008
DOI: 10.1242/jcs.018770
|View full text |Cite
|
Sign up to set email alerts
|

Breaking up is hard to do – membrane traffic in cytokinesis

Abstract: Centrosomes, centriolin and a potential link to secretory membrane traffic Traffic from the trans-Golgi network (TGN) and the secretory pathway to the furrow and/or midbody of dividing cells is thought

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 84 publications
3
105
0
1
Order By: Relevance
“…Cytokinesis involves a rapid and massive expansion in plasma membrane surface area that strongly depends on endocytic and/or secretory membrane trafficking pathways in several cell systems (Albertson et al, 2005;Boucrot and Kirchhausen, 2007;McKay and Burgess, 2011;Neto et al, 2011;Prekeris and Gould, 2008). Previous studies have demonstrated that spermatocyte cytokinesis is sensitive to Brefeldin A (Robinett et al, 2009) and requires the wild-type function of the Golgi proteins Syntaxin 5 (Xu et al, 2002a), Fws , Fwd (Polevoy et al, 2009) and Brunelleschi (Robinett et al, 2009), indicating a requirement for effective Golgi trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinesis involves a rapid and massive expansion in plasma membrane surface area that strongly depends on endocytic and/or secretory membrane trafficking pathways in several cell systems (Albertson et al, 2005;Boucrot and Kirchhausen, 2007;McKay and Burgess, 2011;Neto et al, 2011;Prekeris and Gould, 2008). Previous studies have demonstrated that spermatocyte cytokinesis is sensitive to Brefeldin A (Robinett et al, 2009) and requires the wild-type function of the Golgi proteins Syntaxin 5 (Xu et al, 2002a), Fws , Fwd (Polevoy et al, 2009) and Brunelleschi (Robinett et al, 2009), indicating a requirement for effective Golgi trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mammalian cells and animal model systems have implicated several components of the secretory and endocytic/recycling machineries in cytokinesis (Prekeris and Gould 2008;Neto et al 2011;Giansanti et al 2012;Tang 2012). A proteomics-based analysis of purified midbodies isolated from Chinese hamster ovary cells revealed that the largest proportion of midbody proteins had a known role in secretory and membrane trafficking; the requirement for cytokinesis of many of the homologs was confirmed by RNA interference in C. elegans (Skop et al 2004).…”
Section: Membrane Formation and Composition: Directing Traffic And Dementioning
confidence: 99%
“…Endocytic and recycling proteins are also key players in mediating both furrow ingression and abscission (Prekeris and Gould 2008).…”
Section: Membrane Formation and Composition: Directing Traffic And Dementioning
confidence: 99%
“…The last step of cell division is the physical separation of two daughter cells via a process known as cytokinesis (Barr and Gruneberg, 2007;Prekeris and Gould, 2008). After replication of the genetic material, the mother cell divides by the formation of a cleavage furrow that constricts the cytoplasm, thus leaving two daughter cells connected by a thin intracellular bridge (ICB).…”
Section: Introductionmentioning
confidence: 99%
“…While earlier studies thought this abscission event was simply a continuation of the constriction placed on the cleavage furrow by the actomyosin contractile ring, it was later discovered that abscission is a highly complex and organized event consisting of much more than a simple actin and non-muscle myosin constricting ring. Endocytic membrane transport, ESCRT protein complex function, and cytoskeletal reorganization were all shown to contribute to cytokinesis and abscission (Barr and Gruneberg, 2007;Prekeris and Gould, 2008). The goal of this review is provide an overview the newest advances in our understanding about the dynamics and roles of endosomal transport during cytoskeletal re-arrangements and ESCRT complex assembly throughout cytokinesis.…”
Section: Introductionmentioning
confidence: 99%